A novel method for constructing an acellular 3D biomatrix from bovine spinal cord for neural tissue engineering applications. (19th April 2019) - Arslan, Yavuz Emre; Efe, Burcu; Sezgin Arslan, Tugba
Abstract: In this study, we aimed at generating 3‐dimensional (3D) decellularized bovine spinal cord extracellular matrix‐based scaffolds (3D‐dCBS) for neural tissue engineering applications. Within this scope, bovine spinal cord tissue pieces were homogenized in 0.1 M NaOH and this viscous mixture was molded to attain 3D bioscaffolds. After resultant bioscaffolds were chemically crosslinked, the decellularization process was conducted with detergent, buffer, and enzyme solutions. Nuclear remnants in the native tissue and 3D‐dCBS were determined with DNA content analysis and agarose gel electrophoresis. Afterward, 3D‐dCBS were biochemically characterized in depth via glycosaminoglycan (GAG) content, hydroxyproline (HYP) assay, and sodium dodecyl sulfate‐polyacrylamide gel electrophoresis (SDS‐PAGE). Cellular survival of human adipose‐derived mesenchymal stem cells (hAMSCs) on the 3D‐dCBS for 3rd, 7th, and 10th days was assessed via MTT assay. Scaffold and cell/scaffold constructs were also evaluated with scanning electron microscopy and histochemical studies. DNA contents for native and 3D‐dCBS were respectively found to be 520.76 ± 18.11 and 28.80 ± 0.20 ng/mg dry weight ( n  = 3), indicating a successful decellularization process. GAG content, HYP assay, and SDS‐PAGE results proved that the extracellular matrix was substantially preserved during the decellularization process. In conclusion, it is believed that the novel decellularization method may allow fabricating 3D bioscaffolds with desired geometry from soft nervous system tissues.